Kapłan przewodnikiem ludu Bożego - Sielepin, Adelajda (Studia Pastoralne, 2026)
The article deals with the role of leadership of the ordained priest. This funcion arises from Christ’s Priesthood, which obviously dierects the Church towards the Father. It happens mainly within liturgy, when a priest is a guide both in teaching and in selfoffering to the Father. An important role of a priest as a leader is to evoke in peoples’ hearts a desire for the Holy Spirit (epicletic attitude), who is the ultimate Guide leading to the full Truth. The priestly spirit of leadership is kerigmatic (proclamation of Good news) and mystagogical, because it initiates into the Mystery of salvation through activating peoples’ common priesthood.